Analisa Kelayakan Perkerasan Lentur Ditinjau dari Uji Core Drill (Ruas Jalan Arteri Siring Porong KM 4+970 S.D 4+600) - Muhammad Ubaidillah; Rifki Amirullah; Siti Zainab (Departement of Mathematics Education, 2023)
One of the government's main programs is infrastructure development, which has an important role to shorten the time in the process of national and regional development. To realize good road infrastructure and to support the comfort of road infrastructure users, highway pavements are needed, especially flexible pavements that meet the requirements and are suitable for use. One of the feasibility studies of flexible pavement on the asphalt compaction section carried out in the Sidoarjo-Gempol-Pandaan-Malang-Kepanjen Road and Bridge Preservation Project is by testing the core drill in the field. The core drill test is a method that performs asphalt sampling on a road segment. The sample that has been taken (cylindrical shape) is then taken to the laboratory to be tested for its specific gravity and then compared with the specific gravity of solid asphalt, if the ratio of the two specific gravity is above 98%, the compaction on the road section meets the requirements and is suitable for use. In this journal, an analysis of the feasibility of compacting asphalt will be carried out on the Siring Porong Arterial Road Section Km 4+970 to 4+600 on September 7-8, 2022.